2021
DOI: 10.3389/fphar.2021.778890
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Uric Acid is Associated With Poor Survival in Advanced HCC Patients and Febuxostat Improves Prognosis in HCC Rats

Abstract: Objective: Serum uric acid is associated with tumor progression and hepatocarcinogenesis. Here, we aimed to determine whether serum uric acid is related to the survival time of patients with hepatocellular carcinoma (HCC) and whether the inhibition of uric acid production affects the progression and survival of rats with HCC.Methods: The follow-up data of 288 patients with advanced HCC were analyzed. Ten purine metabolites in serum and liver samples of diethylnitrosamine (DEN)-induced HCC rats were quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Consistent with what we found in pediatric HB patients; emerging evidence of epidemiological studies have linked SUA to liver cancer in adulthood. A retrospective analysis of 288 advanced HCC patients revealed that SUA were negatively correlated with the survival time (15). This was also evidenced by other research showing HCC patients with high pre-operative SUA had worse prognosis after surgery (26).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Consistent with what we found in pediatric HB patients; emerging evidence of epidemiological studies have linked SUA to liver cancer in adulthood. A retrospective analysis of 288 advanced HCC patients revealed that SUA were negatively correlated with the survival time (15). This was also evidenced by other research showing HCC patients with high pre-operative SUA had worse prognosis after surgery (26).…”
Section: Discussionmentioning
confidence: 64%
“…Given that uric acid is mainly produced in the liver from degradation of dietary and endogenous purine compounds, there has been growing interest in the role of SUA playing in the development of liver cancer. Recent report reveals that high SUA could be a significant risk factor of adult liver malignancy, suggesting that SUA contributes to the hepato-carcinogenesis (15). To date, studies investigating the association between SUA and pediatric liver tumor are still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with HCC are diagnosed at an advanced stage, so radical treatment (e.g., liver transplantation or surgery) is not possible ( Javan et al, 2020 ; Wang and Li, 2021 ; Wu et al, 2021 ). In general, HCC is insensitive to various cytotoxic chemotherapeutics, which further limits the treatment strategies for HCC ( Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the metabolic imbalance of purine and uric acid is one of the most significant metabolic changes in cancer, which not only affects the growth of primary tumors but also mediates tumor progression and metastasis ( Wu et al, 2021 ). However, the relationship between purine and uric acid metabolism and the prognosis of patients with HCC has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%